Pengalaman penyelia dalam pengurusan pekerja datang lewat ke tempat kerja : Kajian dalam sektor perindustrian - Elizarohoyih, Anak Acho (Universiti Malaysia Sarawak (UNIMAS), 2015)
Lateness to work is an issue of big discipline problem and a burden to the organization. However, if this problem is not dealt under labor issues systematically the cases of coming late to work will increase. Based on the context of the review by the supervisor it was found that lateness to work is experienced when the workers come after a predetermined work time begins. The main objective of this study was to examine the context of data, reasons and strategies in the management ofemployees coming late to work within the organization. This qualitative research has used the phenomenological approach and thematic analysis. For more information on this study, researcher conducted in-depth interviews with six supervisors, through their experience in the management of employees' lateness to work. Based on this study, researcher found that there were various reasons given by employees when it comes to being late to work. The management strategies were very strict and systematic in order to help supervisors in the management of employees' lateness. Results from this study showed that the reasons they came late through was due to the individuals themselves, their families and the environment. Employees' lateness to work will decrease if the management strategy in organizations always have a positive impact. This is because, based on the experience of supervisors, strict rules on workers' time of arrival to the workplace were set out in the rules and regulations in organization.